Lucifer Season 6 Disc 3 - Ellis, Tom, 1978-; German, Lauren, 1978-; Alejandro, Kevin, 1976-; Cathey, Reg E.; Warner Home Video (Firm) (Burbank, CA Warner Home Video, 2022)
In the sixth and final season of Lucifer, we close the chapter on our crime-solving Devil. With Los Angeles no longer the battleground for his angelic siblings, Lucifer's relationship with Chloe has never been stronger. Life is good. But if we know anything about this fallen angel, it's that his past always finds a way of catching up to him.
Partners 'til the end -- Save the devil, save the world -- Goodbye, lucifer.
Title from container.
Originally broadcast as single episodes of a television program in 2021.
Season six, disc three; episodes 8-10. Contains special features
Tom Ellis, Lauren German, Kevin Alejandro, Reg E. Cathey, Lesley-Ann Brandt, Aimee Garcia, Rachael Harris, Brianna Caitlin Hildebrand.
Rating: Not rated.
DVD, region 1; Dolby digital 5.1; wide screen.
Keywords: Devil -- Drama; Police -- California -- Los Angeles -- Drama; Women detectives -- Drama; Demonology -- Drama; Good and evil -- Drama; Criminal investigation -- Drama; Man-woman relationships -- Drama; Television programs; Fiction television programs; Television crime shows; Fantasy television programs; Video recordings for the hearing impaired